Taxonomy, biology, and efficacy of two Australian parasitoids of the eucalyptus gall wasp, Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae: Tetrastichinae) - Kim, Il-Kwon; Mendel, Zvi; Protasov, Alexey; Blumberg, Daniel; la Salle, John (Zootaxa, 2008)
Two species of Tetrastichinae (Hymenoptera: Eulophidae) from Australia are described as parasitoids of Leptocybe invasa Fisher & La Salle: Quadrastichus mendeli Kim & La Salle sp.nov. and Selitrichodes kryceri Kim & La Salle sp. nov. These parasitoids were introduced to Israel as part of a biological control program to counter the severe levels of damage caused by L. invasa to Eucalyptus plantations throughout the Mediterranean Basin. The biology of these species, as well as their potential as biological control agents, is discussed. Both species are now successfully established in Israel. The parasitoids were collected from L. invasa galls on 3–4 year old Eucalyptus tereticornis trees in central west Queensland, between Gympie and Hervey Bay, and on the Atherton Tableland. Both species are small (about 1 mm in length), solitary, and apparently ectoparasitic wasps. S. kryceri is biparental whereas Q. mendeli is uniparental. Maximum survival (~ 6 days at 25°C) for both species was obtained when they were fed with honey solution. S. kryceri and Q. mendeli successfully parasitized approximately 2.2 and 2.5 gall units per day, respectively. Both species developed on both young and mature host larvae. L. invasa may be considered as an early colonizer of regenerated young stands in Australia, which may imply that its parasitoids will display a similar fast-tracking behavior with respect to their host in its invasive range. The generic status of Selitrichodes is reinstated, with Epomphaloides and Zagrammosomoides placed as new synonyms of Selitrichodes.